Connecting Africa’s Universities to Affordable High-Speed Broadband Internet : What Will it Take? - Bashir, Sajitha (World Bank, Washington, DC, 2020)
Connecting African universities to affordable, high speed broadband internet is essential for attaining the goals of the digital economy for Africa moonshot, which aims to ensure that all African individuals, businesses, and governments are digitally enabled by 2030. Access to the Internet promotes economic growth, improvements to education and knowledge dissemination, and overall human development. The advanced digital skills of high quality, that are needed to adapt and exploit digital technologies, will need to be produced through reformed university programs and rapid skills development programs. Intermediate level digital skills that are needed on a broad scale for the diffusion of technologies will be produced on a large scale when all African tertiary level students (not just those in science and engineering courses) acquire adequate levels of digital competence. African universities need broadband in order to expand coverage, through blended and online learning; improve the quality of higher education; encourage the use of technology in higher education; and provide access to the enormous wealth of digital education resources available in the world and enable Africans to contribute their own digital content. Connecting Africa’s universities will also have spillover effects on the broader education system, especially secondary schools and technical-vocational institutions, where teachers and students need to acquire intermediate and basic digital skills.